Service Quality Disparities in Public Healthcare: A Comparative Study of Customer Expectations and Perceptions in Urban and Remote Areas of Indonesia - Siti Sofiaturrohmah; Andi Kasman (Dealings Foundation Institute, 2025)
This study aims to analyze the gap between public expectations and perceptions of healthcare services in Indonesia, with a focus on four regions: DKI Jakarta, DI Yogyakarta, Papua, and Maluku. Employing a qualitative approach, the research is based on secondary data analysis to evaluate both customer expectations and perceived service quality. The findings reveal a significant disparity between what citizens expect and what they experience, particularly influenced by factors such as service quality, communication, infrastructure, and demographic characteristics. Regions with limited geographical accessibility and underdeveloped infrastructure—such as Papua and Maluku—demonstrate notably more negative perceptions compared to more urbanized areas like DKI Jakarta and DI Yogyakarta. The study concludes that addressing this gap requires strategic interventions, including improving healthcare worker competencies, leveraging appropriate technological innovations, and fostering honest and transparent communication between providers and patients. The study recommends continuous professional training for medical personnel, substantial investment in healthcare infrastructure, and the establishment of effective patient feedback mechanisms. These measures are essential to enhance patient satisfaction, build public trust, and strengthen loyalty toward healthcare services in Indonesia.